2020
DOI: 10.1111/btp.12860
|View full text |Cite
|
Sign up to set email alerts
|

Climate and plant structure determine the spatiotemporal butterfly distribution on a tropical mountain

Abstract: Mountains are among the most powerful natural gradients for testing ecological and evolutionary responses of biota to environmental influences because differences in climate and plant structure occur over short spatial scales. We describe the spatiotemporal distribution patterns and drives of fruit‐feeding butterfly diversity in the mountainous region of Serra do Cipó, Minas Gerais, Brazil. Seven elevations from 822 to 1,388 m a.s.l. were selected for evaluating the effects of abiotic factors and vegetation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Rainy season might probably affect negatively Lepidoptera life, especially their dispersal and egg‐laying activity (Maicher et al, 2018) and that would help to explain the rainy season‐low abundance and species richness in NNP. However, in Neotropical regions (Beirão et al, 2021; DeVries & Walla, 2001) and in some semi‐arid tropical ecosystems (Nobre et al, 2012), the rainy seasons show more abundance for fruit‐feeding butterflies, especially canopy species than the dry seasons. Hence, a study on vertical stratification of Nyungwe butterflies including canopy species would help clearly assess the effect of seasonality on the distribution of fruit‐feeding butterflies in the Nyungwe mountain forest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rainy season might probably affect negatively Lepidoptera life, especially their dispersal and egg‐laying activity (Maicher et al, 2018) and that would help to explain the rainy season‐low abundance and species richness in NNP. However, in Neotropical regions (Beirão et al, 2021; DeVries & Walla, 2001) and in some semi‐arid tropical ecosystems (Nobre et al, 2012), the rainy seasons show more abundance for fruit‐feeding butterflies, especially canopy species than the dry seasons. Hence, a study on vertical stratification of Nyungwe butterflies including canopy species would help clearly assess the effect of seasonality on the distribution of fruit‐feeding butterflies in the Nyungwe mountain forest.…”
Section: Discussionmentioning
confidence: 99%
“…Butterflies are among the well‐documented insects all over the world, but when compared to temperate regions, little is known about the ecology of tropical butterflies (Bonebrake et al, 2010). Moreover, within the tropics, little is known for example about fruit‐feeding butterflies' distribution and ecology in Afrotropical regions (Aduse‐Poku et al, 2012; Maicher et al, 2019; Molleman et al, 2006; Oloya et al, 2021; Valtonen et al, 2013), compared with Neotropics (Beirão et al, 2021; DeVries et al, 2012; DeVries & Walla, 2001; Morina‐Martínez et al, 2013; dos Santos et al, 2017; Whitworth et al, 2016). It appears from the literature that studies on Afrotropical fruit‐feeding butterflies' diversity have been conducted in low lands (Bobo et al, 2006; Molleman et al, 2006; Nkongolo & Bapeamoni, 2018; Nyafwono et al, 2014; Roche et al, 2015), but few have been conducted in high mountain tropical ecosystems, (Maicher et al, 2019) although these mountains are biodiversity‐rich due to their diverse habitat types across elevation gradient (Spehn et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have revealed marked patterns of species turnover in butterfly communities with increasing elevation (Acharya & Vijayan, 2015;Beirão et al, 2020;Fleishman et al, 1998;Kocher & Williams, 2000;Maicher et al, 2020;Molina-Martínez et al, 2016;Pires et al, 2020;Pyrcz & Wojtusiak, 2002;Pyrcz et al, 2009;Wagner et al, 2013), as well as an effect of topography on butterfly composition (Binz et al, 2015;Fleishman & Nally, 2002). Due to the greater influence of species replacement on beta-diversity in riverbeds, we found that the butterfly community at this topographic position became segregated as elevation increased, with two sets of species: one associated with the low parts of the gradient and the other associated with the high parts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies evaluated the composition and diversity of Lepidoptera along elevational gradients in Brazil (CARNEIRO et al, 2014;FERNANDES et al, 2016;PEREIRA et al, 2017;HENRIQUES et al, 2019;BEIRÃO et al, 2020;PIRES et al, 2020). However, data related to the influence of elevation on Lepidoptera communities in Brazil are still scarce and many elevation zones remain to be studied (HENRIQUES et al, 2019), especially considering its large territorial extension.…”
Section: Introductionmentioning
confidence: 99%